Size and Treatment Outcomes of HR+, HER2- Early Breast Cancer Population With High Risk of Recurrence: A Real-World Cohort Study With Danish Breast Cancer Cooperative Group Registry Data - Heidi Loponen; Juha Mehtälä; Laila Mehkri; Astrid Torstensson; Anna Emde; Tero Ylisaukko-oja; Walid Fakhouri (Journal of Health Economics and Outcomes Research, 2025)
# Background While the prognosis is generally good for hormone receptor–positive (HR+), human epidermal growth factor–negative (HER2–) early breast cancer (EBC) patients, up to 30% of patients with high-risk clinical and/or pathologic features experience recurrence.